2015
DOI: 10.2298/psi1501005j
|View full text |Cite
|
Sign up to set email alerts
|

More than a (negative) feeling: Validity of the perceived stress scale in Serbian clinical and non-clinical samples

Abstract: The goal of the present study was to test the validity of a Serbian version of the Perceived Stress Scale. The PSS was administered to 157 psychiatric outpatients, 165 adults from the non-clinical population, and 283 university students. The results of the confirmatory factor analysis supported a bifactor model of the PSS with one general factor and two specific factors reflecting perceived distress and perceived self-efficacy. Internal consistencies of the scale and its two subscales were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 32 publications
11
41
2
3
Order By: Relevance
“…Cronbach's alpha values in this current study revealed that not only the overall PSS-14 and PSS-10, but also each of the two subscales of PSS-14 and PSS-10 were internally reliable, but PSS-4 was not. These findings were in line with previous studies in different countries, such as China [23], Japan [14], Vietnam [20], Korea [28], Thailand [22], Arabia [17], America [29,30], Brazil [21], Greece [11,31], Mexico [12], Germany [19], Sweden [9,15] and Serbia [18]. Few study showed acceptable reliability of PSS-4, such as the United Kingdom [32], French workers [10] and American survivors of suicide [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cronbach's alpha values in this current study revealed that not only the overall PSS-14 and PSS-10, but also each of the two subscales of PSS-14 and PSS-10 were internally reliable, but PSS-4 was not. These findings were in line with previous studies in different countries, such as China [23], Japan [14], Vietnam [20], Korea [28], Thailand [22], Arabia [17], America [29,30], Brazil [21], Greece [11,31], Mexico [12], Germany [19], Sweden [9,15] and Serbia [18]. Few study showed acceptable reliability of PSS-4, such as the United Kingdom [32], French workers [10] and American survivors of suicide [13].…”
Section: Discussionsupporting
confidence: 91%
“…The PSS has been translated into many languages and the reliability and validity have been verified in different countries. For instance, PSS-14 has been evaluated in Sweden [9], France [10], Greece [11], Mexico [12], America [13] and Japan [14]; PSS-10 has been evaluated in Sweden [15], France [10], Korea [16], Mexico [12], America [13], Arabia [17], Serbia [18], Germany [19], Vietnam [20], Brazil [21] and Thailand [22]; PSS-4 has been evaluated in France [10], Korea [16], Mexico [12] and America [13]. In China, a few studies have verified the PSS in specific population, such as policewomen (PSS-10) [23], university students (PSS-10) [24], elderly service workers (PSS-10) [25] and cardiac patients who smoke (PSS-14, 10 and 4) [26].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that while perceived distress and perceived coping factors exist separately, the PSS-10 is driven by a single underlying dimension of the former. Ultimately, these results are consistent with those of previous studies [20,34] and indicate that both the total and subscale scores of the PSS are usable, as the measure is found to be sufficiently unidimensional. This is a significant outcome that substantiates the unidimensionality assumption of the PSS-10, supporting Cohen and Williamson's (1988) original validation report confirming its unidimensionality.…”
Section: Cfa Of Pss-10supporting
confidence: 90%
“…Recently, two studies proposed a bifactor model of the PSS-10 comprised of a single underlying general factor of perceived stress and two domain-specific factors composed of negatively (Factor 1) and positively (Factor 2) worded items (Jovanović and Gavrilov-Jerković, 2015; Wu and Amtmann, 2013). In a bifactor model, all items load onto a general factor representing the target construct (perceived stress) intended to be assessed by a measure (PSS-10), as well as one of the domain-specific factors.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Amtmann (2013) also concluded that the PSS-10 was sufficiently unidimensional, as the general factor of perceived stress accounted for greater variance than either of the domain-specific factors, and thus supported the use of the PSS-10 total score. Conversely, Jovanović and Gavrilov-Jerković (2015) suggested that both the total and subscale scores of the PSS-10 could be used, although variance explained by the general or domain-specific factors was not evaluated or reported. Further examination of the scale’s dimensionality using a bifactor approach is needed to determine whether the PSS-10 best represents a single dimension (total score) or different dimensions (subscale scores) of perceived stress, or whether both total and subscale scores should be used.…”
Section: Introductionmentioning
confidence: 99%